Accurate prediction of target dose-escalation and organ-at-risk dose levels for non-small cell lung cancer patients. Issue 3 (December 2015) - Petit, Steven F.; van Elmpt, Wouter
Abstract: Purpose/objective: To develop a method to predict feasible organ-at-risk (OAR) and tumour dose levels of non-small cell lung cancer (NSCLC) patients prior to the start of treatment planning. Materials/methods: Included were NSCLC patients treated with volumetric modulated arc therapy according to an institutional isotoxic dose-escalation protocol. A training cohort ( N = 50) was used to calculate the average dose inside the OARs as a function of the distance to the planning target volume (PTV). These dose–distance relations were used in a validation cohort ( N = 39) to predict dose–volume histograms (DVHs) of OARs and PTV as well as the maximum individualized PTV dose escalation. Results: The validation cohort showed that predicted and achieved MLD were in agreement with each other (difference: −0.1 ± 1.9 Gy, p = 0.81). The spinal cord was dose limiting in only two patients, which was correctly predicted. The achieved mean PTV dose varied from 52 to 73 Gy and was predicted correctly with an accuracy better than 2 Gy (i.e. 1 fraction) for 79% of the patients. Conclusion: We have shown that the MLD and the prescribed PTV dose could be accurately predicted for NSCLC patients. This method can guide the treatment planner to achieve optimal OAR sparing and tumour dose escalation.